Analyzing fracture patterns in theran wall paintings - Shin, H.; Doumas, C.; Funkhouser, T.; Rusinkiewicz, S.; Steiglitz, K.; Vlachopoulos, A.; Weyrich, Tim (VAST 2010 - 11th International Symposium on Virtual Reality, Archaeology and Intelligent Cultural Heritage, 2010)
In this paper, we analyze the fracture patterns observed in wall paintings excavated from Akrotiri, a Bronze Age Aegean city destroyed by earthquakes preceding a volcanic eruption on Thera (modern Santorini) around 1630 BC. We use interactive programs to trace detailed fragment boundaries in images of manually reconstructed wall paintings. Then, we use geometric analysis algorithms to study the shapes and contacts of those fragment boundaries, producing statistical distributions of lengths, angles, areas, and adjacencies found in assembled paintings. The result is a statistical model that suggests a hierarchical fracture pattern, where fragments break into two pieces recursively along cracks nearly orthogonal to previous ones. This model could be useful for predicting fracture patterns of other wall paintings and/or for guiding future computer-assisted reconstruction algorithms.
CRIS-Team Scopus Importer:2022-07-26